Cancer Cell Culture Techniques, Micronutrients, and Protocols in Health Sciences: A Comprehensive Review - Zahid, Zunaira; Gencoglu, Hasan (My University, 2024)
Cancer cell culture techniques play a pivotal role in advancing our understanding of cancer biology, drug development, and personalized medicine in the field of health sciences. In order to understand how micronutrients affect the activity, viability, and genomic stability of cells in cancer research, these nutrients must be added to procedures for growing cancer cells. Essential elements that impact DNA metabolism, cell viability, and genomic integrity are micronutrients, which comprise minerals and vitamins. Research revealed that in cancer cell cultures, micronutrients can improve cell viability and preserve genomic integrity. Micronutrients, including vitamins and minerals, are essential components of cell culture media that are designed to promote cell growth and maintain the cells in an in vitro environment. These micronutrients play crucial roles in various cellular functions, including metabolism, DNA synthesis, and antioxidant defense. While micronutrients are generally beneficial for cancer cell growth, it's important to carefully balance their concentrations in cell culture media to avoid adverse effects such as apoptosis. Micronutrients and cancer outcomes have been found to have complex relationships, with varying but significant effects on cancer types and cancer outcomes. Additionally, micronutrients have a critical role in the pathophysiology of cancer by modifying signaling pathways, adding to the complexity of the disease. This review aims to explore the significance of cancer cell culture techniques and the role of micronutrients in cancer research and therapy. Micronutrients must be incorporated into cancer cell growth techniques in health sciences labs in order to preserve genome integrity and cellular viability. Studies revealed that micronutrients play a major role in cellular health through their impact on DNA metabolic pathways. The acknowledgement of their significance in experimental procedures highlights the progress in comprehending their function. As a result, improving the micronutrient content of cell culture supplements has the potential to increase the validity of results and expand knowledge of cancer cell biology.
Keywords: Onkoloji; Biyokimya ve Moleküler Biyoloji